2020
DOI: 10.1200/po.20.00016
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Assessment of Tumor Purity and Its Clinical Implications

Abstract: PURPOSE The tumor microenvironment is complex, comprising heterogeneous cellular populations. As molecular profiles are frequently generated using bulk tissue sections, they represent an admixture of multiple cell types (including immune, stromal, and cancer cells) interacting with each other. Therefore, these molecular profiles are confounded by signals emanating from many cell types. Accurate assessment of residual cancer cell fraction is crucial for parameterization and interpretation of genomic analyses, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…When interpreting the data, tumor content and heterogeneity of tested samples should be considered. 75 Since the fraction of non-tumor cells affects the sensitivity of every assay, it is advisable to evaluate tumor content appropriately. 75 For the integrated analysis of all markers covered by LYNX, a sample should contain at least 20% of tumor cells to ascertain clonally expanded molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…When interpreting the data, tumor content and heterogeneity of tested samples should be considered. 75 Since the fraction of non-tumor cells affects the sensitivity of every assay, it is advisable to evaluate tumor content appropriately. 75 For the integrated analysis of all markers covered by LYNX, a sample should contain at least 20% of tumor cells to ascertain clonally expanded molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, pathologists inspect stained tissue slides to determine tumor cellularity, an approach that is not just laborious but also highly subjective due to intraobserver and interobserver variability. Tumor cellularity can also be inferred computationally from NGS datasets, but there is limited concordance among available inference methods and heavy dependence on the presence of high numbers of genomic alterations for adequate accuracy (55). To address this task using an AI approach, Akbar 53 patients with breast cancer using DNN (InceptionNet architecture), eliminating the need for nuclei segmentation and classification, and feature extraction (56).…”
Section: Characterizing the Tumor Microenvironmentmentioning
confidence: 99%
“…It also provides information about the spatial organization of the tumor microenvironment. Furthermore, previous studies showed that percent tumor nuclei estimates by different pathologists are not only inconsistent but also different from genomic tumor purity values [4,12]. However, we still do not know the causes of the difference.…”
Section: Introductionmentioning
confidence: 77%
“…A sample selected based on an overestimated tumor purity, for example, may lead to a false-negative test result, which may withhold a patient from getting highly promising therapies [5]. Besides, the genomic analysis should incorporate the tumor purity to account for normal cell contamination, which can directly confound results and subsequent clinical decisions [4,[8][9][10][11][12][13]. A novel immunotherapy gene signature missed by traditional methods, for example, was discovered using a differential expression analysis incorporating tumor purity [4].…”
Section: Introductionmentioning
confidence: 99%